2009
DOI: 10.5194/nhess-9-2073-2009
|View full text |Cite
|
Sign up to set email alerts
|

RST analysis of MSG-SEVIRI TIR radiances at the time of the Abruzzo 6 April 2009 earthquake

Abstract: Abstract. Space-time fluctuations of Earth's emitted Thermal Infrared (TIR) radiation have been observed from satellite months to weeks before earthquakes occurrence.The general RST approach has been proposed in order to discriminate normal (i.e. related to the change of natural factor and/or observation conditions) TIR signal fluctuations from anomalous signal transient possibly associated to earthquake occurrence. In this work RST approach is applied to the Abruzzo 6 April 2009 event (M L =5.8) by using for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 36 publications
(29 reference statements)
4
63
0
Order By: Relevance
“…For instance, the RST approach has already been implemented on TIR radiances collected both by polar (NOAA/AVHRR and EOS/MODIS) and geostationary (MSG/SEVIRI) satellite sensors Genzano et al, 2010Genzano et al, , 2009bPergola et al, 2010) to study the Abruzzo seismic event.…”
Section: The Rst Methodology For a Robust Estimation Of Thermal Anomamentioning
confidence: 99%
“…For instance, the RST approach has already been implemented on TIR radiances collected both by polar (NOAA/AVHRR and EOS/MODIS) and geostationary (MSG/SEVIRI) satellite sensors Genzano et al, 2010Genzano et al, , 2009bPergola et al, 2010) to study the Abruzzo seismic event.…”
Section: The Rst Methodology For a Robust Estimation Of Thermal Anomamentioning
confidence: 99%
“…The RST method is based on a preliminary multi-temporal analysis on several years of satellite TIR records, which is devoted to characterize the TIR signal for each pixel of the satellite image processed. This previous study concluded that, anomalous TIR could be identified within TIR data related to an earthquake (Tramutoli et al, 2001Filizzola et al, 2004;Aliano et al, 2007Aliano et al, , 2008Genzano et al, 2009Genzano et al, , 2010Pergola et al, 2010). Each step of the RST method for detecting seismic anomalies using bi-angular Advanced Along-Track Scanning Radiometer data will be explained and detailed in the following.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a data analysis technique named the robust satellite data analysis technique (RST) (Tramutoli, 2007) has been proposed for natural and environmental hazards monitoring and mitigation. This technique has already been validated in the case of many earthquakes (Tramutoli et al, 2001Filizzola et al, 2004;Corrado et al, 2005;Aliano et al, 2007Aliano et al, , 2008Genzano et al, 2007Genzano et al, , 2009Genzano et al, , 2010Pergola et al, 2010).…”
Section: P Xiong Et Al: Detecting Seismic Ir Anomalies In Bi-angulamentioning
confidence: 99%
“…It provides further identification of signal anomalies by an automatic, unsupervised change detection step. RST has already successfully found application in other fields of environmental monitoring, like forest fire detection (Cuomo et al, 2001;Mazzeo et al, 2007;Baldassarre et al, 2009), floods (Lacava et al, 2005(Lacava et al, , 20062010a, b;Faruolo et al, 2009), and volcanic eruptions (Pergola et al, , 2004a(Pergola et al, , b, 2009Bonfiglio et al, 2005; monitoring, seismic areas investigation Di Bello et al, 2004;Corrado et al, 2005;Genzano et al, 2007Genzano et al, , 2009Lisi et al, 2010), etc. Briefly, the technique is based on the preliminary characterization of AVHRR radiances in normal (i.e.…”
Section: Methodsmentioning
confidence: 99%